Kapan Investor Bereaksi? Studi Empiris Dampak Kasus Korupsi Korporat Terhadap Return Saham - Rahel, Herlina Kristin (Keizai, 2025)
This study aims to determine the point at which the disclosure of corruption cases has the greatest impact on stock returns. The study also seeks to examine the effect of corruption case disclosure on stock returns. The study uses cross-sectional data with a quantitative data type and a sample size of 7 companies involved in corruption cases in 2024 and 2025. This research consisted of 29 regressions that were conducted to answer the research questions. The results show that the stock market reacts two days after the disclosure of corruption cases, meaning that investors react on the second day after negative information about the corruption case is circulated. The study also consistently found in many regressions that corruption disclosure negatively affects the company's stock returns.